2023
DOI: 10.3390/biom13020245
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Fermented Beverage with Chlorella vulgaris Powder on Soybean-Based Fermented Beverage

Abstract: The area of functional beverages made from plant-based or non-dairy milk is one of the fastest-growing sectors in the world. The microalgae Chlorella vulgaris is a source of functional ingredients, with a large spectrum of healthy compounds, such as canthaxanthins, astaxanthins, peptides, and oleic acid. The study aimed to investigate the suitability of C. vulgaris biomass as a substrate for Lactobacillus fermentum and Lactobacillus rhamnosus development and fermentation in vegetal soy beverages and to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 62 publications
1
5
1
Order By: Relevance
“…Regarding the concentration of sea buckthorn syrup and fermentation temperature, the drink with a concentration of 20% was more effective than the drink with a concentration of 5%. The results obtained in this study agree with previous studies [67][68][69].…”
Section: Discussionsupporting
confidence: 93%
“…Regarding the concentration of sea buckthorn syrup and fermentation temperature, the drink with a concentration of 20% was more effective than the drink with a concentration of 5%. The results obtained in this study agree with previous studies [67][68][69].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the antioxidant activity is attributed to the presence of various chemical compounds, including chlorophyll derivatives, terpenoids, and carotenoids. Previous studies with Cv have demonstrated the antioxidant effects of the microalgae [ 60 , 61 ] and those included in foods [ 62 , 63 ], however, CvG, having lower chlorophyll content due to a mutation, could decrease the antioxidant effect of CV-AN provided by macroalgae with phlorotannin [ 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Radical scavenging activity and phenolic content as well as minerals (calcium an iron) improved after fermentation. C. vulgaris and soy extract fermented using Lactobacillus fermentum and Lactobacillus rhamnosus resulted in improved polyphenol content and dietary antioxidant capacity compared to fermented soy extract [78]. Fermentation mitigated plant protein allergens resulted in the loss of the IgE-binding ability of epitopes [9,79].…”
Section: Impact Of Fermentation On Thementioning
confidence: 99%